2020
DOI: 10.1093/cid/ciaa1383
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Routine Testing for Coronavirus Disease 2019 (COVID-19) in High-risk Healthcare Environments to Reduce Outbreaks

Abstract: Routine asymptomatic testing strategies for COVID-19 have been proposed to prevent outbreaks in high-risk healthcare environments. We used simulation modeling to evaluate the optimal frequency of viral testing. We found that routine testing substantially reduces risk of outbreaks, but may need to be as frequent as twice weekly.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
82
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(95 citation statements)
references
References 11 publications
10
82
2
1
Order By: Relevance
“…Testing 2-3 times per week is suggested for optimal public health impact. 20 In the UK, screening showed lower sensitivity when tests were performed by testers who were not health care workers than when they were performed by health care workers; however, the discrepancy disappeared over a 2-week period, which suggests that workers who are not trained in health care can be taught with experience to adequately perform swabs. 16 Preprint research has shown that self-testing may have similar performance to swabs taken by professionals, 21 and home-based use needs urgent evaluation to facilitate scalability and minimize biosafety concerns.…”
Section: How Can Rapid Antigen Testing Be Incorporated Into Canada'smentioning
confidence: 98%
“…Testing 2-3 times per week is suggested for optimal public health impact. 20 In the UK, screening showed lower sensitivity when tests were performed by testers who were not health care workers than when they were performed by health care workers; however, the discrepancy disappeared over a 2-week period, which suggests that workers who are not trained in health care can be taught with experience to adequately perform swabs. 16 Preprint research has shown that self-testing may have similar performance to swabs taken by professionals, 21 and home-based use needs urgent evaluation to facilitate scalability and minimize biosafety concerns.…”
Section: How Can Rapid Antigen Testing Be Incorporated Into Canada'smentioning
confidence: 98%
“…Models of similar settings have also found the frequency of testing required to control outbreaks can be dependent on community prevalence. 19 The timing of this transition, and how it should be implemented, may be an important area for future work.…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 99%
“…Several modeling studies now support mass testing in healthcare settings to prevent asymptomatic spread. 5 , 6 Our experience suggests there could be substantial benefit in encouraging testing of staff with any degree of symptoms, even mild because up to half of positive HCP would be detected by this strategy.…”
Section: Discussionmentioning
confidence: 98%